Relevansi Filsafat Bahasa dalam Memahami Al-Qur’an - Zulqurnain, Muhammad; Roni Subhan (SETYAKI : Jurnal Studi Keagamaan Islam, 2024)
Philosophy of language is a branch of philosophy that studies the nature, structure and function of language. In the context of understanding the Qur'an, the philosophy of language has significant relevance. The Koran is the holy book in Islam which is considered a revelation from Allah to the Prophet Muhammad. To understand the messages and teachings contained in the Koran, it is important to understand the Arabic language used in its writing. Philosophy of language helps in understanding the structure and meaning of the Arabic language used in the Qur'an. Through philosophical analysis, we can understand the grammar, semantics and pragmatics used in the verses of the Qur'an. For example, understanding the meaning of words, concepts, and the relationship between words in sentences can help us understand the message the Al-Qur'an wants to convey. Apart from that, the philosophy of language also helps in understanding the social and historical context behind the use of language in the Qur'an. Language is a cultural product and reflects the thoughts and values ​​of society at that time. By understanding the social and historical context, we can interpret the verses of the Koran more accurately and understand the message we want to convey in the right context. Apart from that, the philosophy of language also helps in understanding the metaphysical and symbolic aspects of the Koran. Language has strong symbolic power, and the Qur'an uses language in a distinctive way to convey spiritual and metaphysical messages. Through philosophical analysis, we can understand the symbolic and metaphysical meaning contained in the verses of the Qur’an.